PENGARUH KOMPENSASI FINANSIAL DAN NON FINANSIAL TERHADAP MOTIVASI KERJA DAN KINERJA KARYAWAN BAGIAN LAPANGAN PADA PT UNITED SINDO PERKASA - Novi Indriani; Adhitomo Wirawan (Politeknik Negeri Batam, 2019)
This study aims to identify, both simultaneously and partially between financial and non-financial compensation for employees and employees of PT United Sindo Perkasa. This research use Multiple Linear Regression method. The sample in this study used total sampling technique where everyone. The research instrument used is interview and questionnaire. The result of this research is positive financial compensation variable to work motivation. It is seen from tcount (3,203) bigger than ttable (1,66) with significant level (0,002 < 0,05). The non-financial compensation variable has an effect on work, different from 2,461 with significant level (0,007 < 0,05). Simultaneously, between financial and non-financial tax compensation variable on work motivation, it is seen from Fcount (13,451) bigger than Ftable (3.11) with significant level (0,000 < 0,05). Financial compensation variable has a positive effect on employee performance, different from ttable (1.66) with significant level (0,005 < 0,05). Non-financial compensation positive variable on employee performance, different from ttable (1.66) with significant level (0,023 < 0,05). Adjacent simultaneously between financial compensation variables and non-financial compensation on employee performance, this is seen from Fcount (10,312) greater than Ftable (3.11) with significant level (0,000 < 0.05).